The Therapeutic Potential of Regulatory T Cells: Challenges and Opportunities - Bayati, Fatemeh; Mohammadi, Mahsa; Valadi, Maryam; Jamshidi, Saeid; Foma, Arron Munggela; Sharif-Paghaleh, Ehsan (Frontiers in Immunology, 2021)
Regulatory T cells (Tregs), are an immunosuppressive subgroup of CD4+ T cells which are identified by the expression of forkhead box protein P3 (Foxp3). The modulation capacity of these immune cells holds an important role in both transplantation and the development of autoimmune diseases. These cells are the main mediators of self-tolerance and are essential for avoiding excessive immune reactions. Tregs play a key role in the induction of peripheral tolerance that can prevent autoimmunity, by protecting self-reactive lymphocytes from the immune reaction. In contrast to autoimmune responses, tumor cells exploit Tregs in order to prevent immune cell recognition and anti-tumor immune response during the carcinogenesis process. Recently, numerous studies have focused on unraveling the biological functions and principles of Tregs and their primary suppressive mechanisms. Due to the promising and outstanding results, Tregs have been widely investigated as an alternative tool in preventing graft rejection and treating autoimmune diseases. On the other hand, targeting Tregs for the purpose of improving cancer immunotherapy is being intensively evaluated as a desirable and effective method. The purpose of this review is to point out the characteristic function and therapeutic potential of Tregs in regulatory immune mechanisms in transplantation tolerance, autoimmune diseases, cancer therapy, and also to discuss that how the manipulation of these mechanisms may increase the therapeutic options.